Preliminary design of 19 passengers multipurpose airplane / Mohd Taha Abdul Rauf - Abdul Rauf, Mohd Taha (2002)
The objective of this project is to do preliminary design of 19 passengers multipurpose airplane. The airplane configuration consists of high wing, two turboprop engines, conventional tail and non-retractable tricycle landing gear. The airplane is designed according FAR 23 regulation. The aircraft operates at the rural to urban area. The analysis involves parametric sizing, undercarriage layout, weight and balance, stability in static longitudinal and flight performance. It is shown that the airplane is stable (static longitudinal) by having negative C ma. In the end, the design requirement and actual perform will be compared.